Pemanfaatan Media Peta dalam Pembelajaran IPS Kelas V di MI Al-Muniroh 1 Ujung Pangkah - Taseman; I Kartikasari; M W Laili; Muzdalifa; S Maryam; Iman Rasiman (JIEES : Journal of Islamic Education at Elementary School, 2020)
The purpose of making this journal is to find out the availability and use of learning media for map learning in Social Sciences (IPS) class V at MI Al-Muniroh 1, as well as to find out the efforts made by teachers in utilizing the learning media for maps. As well as to describe the response of teachers and students to the map as a medium of learning, find out the attractiveness of the media of learning maps based on the results of an online questionnaire, and find out the increase in student learning outcomes after using the learning media of the map. The research method used in this study is a quantitative research method, which is a method that uses data from the results of a questionnaire that has been distributed and filled out by the fifth grade students of MI Al-Muniroh 1 Ujung Pangkah. From the observations of 100% of fifth grade students of MI Al-Muniroh 1 Ujung Pangkah agree that map learning media has an effect on improving student learning outcomes because with the learning media map, students can more easily understand the explanations explained by the teacher.